Final answer:
The equation a. 6x + 1 = 3(2x - 4) has no solution, while the other equations have solutions.
Step-by-step explanation:
The equation 6x + 1 = 3(2x - 4) can be simplified as follows:
- 6x + 1 = 6x - 12
- 1 = -12
Since the equation is contradictory, it has no solution.
Similarly, the equation 2 - 5x = 7x - 12 can be simplified as follows:
- 2 + 12 = 7x + 5x
- 14 = 12x
- x = 14/12
The solution x = 7/6 is a valid solution, so this equation does have a solution.
For the remaining equations, it can be observed that they can be simplified as:
- 4(3 - x) = 2(6 - 2x) simplifies to 12 - 4x = 12 - 4x, which is an identity with infinitely many solutions.
- 5(x + 2) = 2(x - 4) simplifies to 5x + 10 = 2x - 8, which can be further simplified as 3x = -18, and x = -6. Hence, this equation does have a solution.
- -4(x + 3) = 4(x - 1) simplifies to -4x - 12 = 4x - 4, which can be further simplified as -12 = 8x, and x = -3/2. This equation does have a solution.
In conclusion, the equations that have no solution are: a. 6x + 1 = 3(2x - 4).